Inclusion-light or innovation of inclusion: modes of innovation and exnovation for the German vocational rehabilitation and participation system - York, Jana; Jochmaring, Jan (Frontiers in Rehabilitation Sciences, 2024)
This paper examines the German system of vocational rehabilitation and participation from a system- and innovation-theoretical perspective. The German system of vocational rehabilitation and participation, with its established special systems for participation in the labor market, is facing a - long overdue - reorientation. The article presents central instruments of the vocational rehabilitation system based on legal foundations, official labor market statistics, and current research findings. The authors compare the legal requirements for an inclusive work environment with the actual employment situation of people with disabilities and highlight a central dilemma of inclusion. Two modes of innovation and exnovation in the vocational rehabilitation system are proposed and critically discussed to resolve the dilemma.